Whey protein concentrate gels with honey and wheat flour - Yamul, Diego Karim (2005)
Structural and functional properties of whey protein concentrate gels with different honey and wheat flour contents, prepared at pHs 3.75, 4.2 and 7.0, were analysed. Gel structure was observed by scanning electron microscopy. The apparent transition temperatures for protein denaturation and starch gelatinization were determined by differential scanning calorimetry. Gels were characterised through solubility assays in different extraction solutions and polyacrylamide gel electrophoresis of the soluble protein components. The firmness, elasticity, relaxation time, adhesivity and cohesiveness of gels were determined, and the water-holding capacity and superficial colour of gels were also studied. Results suggest that wheat flour could interact with whey proteins, and produces a decrease in the protein solubility of whey protein concentrate gels, and in the temperature of whey protein denaturation. The effect of wheat flour on the functional properties of whey protein concentrate gels was different at acidic than at neutral pH: the presence of wheat flour produced an increase in the relaxation time and in the cohesiveness of gels prepared at pH 3.75, whereas at neutral pH a decrease in both properties was observed. Honey and flour content increased the water-holding capacity and browning of WPC gels.